Relationship between Knowledge, Age, Parity, and History of Fe Tablet Consumption with the Occurrence of Anemia in Pregnant Women - Nina Yusnia; Annisa Fitri NR; Amelia Septi (International Journal of Health and Social Behavior, 2025)
The cases of maternal mortality Bogor city in 2022 caused anemia were found to be 30.77%. The purpose the study to determine the relationship between Knowledge, Age, Parity, and History Fe tablet consumption with the incidence of anemia in pregnant women PMB Muthia, Amd.keb Cilendek Barat Bogor Barat, Bogor City in 2024. Research with quantitative approach, cross-sectional design. The sample selected using total sampling technique. Data collected through questionnaires and medical records consisting 42 respondents. variables of knowledge, parity, age, history Fe tablet consumption, and anemia. The research data were interpreted using Chi Square. Based on the calculation results, was found that among 42 respondents, those with poor knowledge more prevalent the non-anemic group, with 8 people (100.0%), compared anemic group, with 24 people (70.6%). Based on calculation results obtained from 42 respondents, those with age and parity were at greater risk anemia group with 12 people (35.3%) compared to the non-anemia group with 0 people (0.0%). Based calculation results obtained from 42 respondents, those with a history of Fe tablet consumption had higher risk in the anemia group, with 19 people (55.9%) compared non-anemia group, with 3 people (37.5%). There relationship between parity, maternal age, and incidence anemia.